Bacteriophages and Their Role in Food Safety - Sanna M. Sillankorva; Hugo Oliveira; Joana Azeredo (International Journal of Microbiology)
The interest for natural antimicrobial compounds has increased due to alterations in consumer positions towards the use of chemical preservatives in foodstuff and food processing surfaces. Bacteriophages fit in the class of natural antimicrobial and their effectiveness in controlling bacterial pathogens in agro-food industry has led to the development of different phage products already approved by USFDA and USDA. The majority of these products are to be used in farm animals or animal products such as carcasses, meats and also in agricultural and horticultural products. Treatment with specific phages in the food industry can prevent the decay of products and the spread of bacterial diseases and ultimately promote safe environments in animal and plant food production, processing, and handling. This is an overview of recent work carried out with phages as tools to promote food safety, starting with a general introduction describing the prevalence of foodborne pathogens and bacteriophages and a more detailed discussion on the use of phage therapy to prevent and treat experimentally induced infections of animals against the most common foodborne pathogens, the use of phages as biocontrol agents in foods, and also their use as biosanitizers of food contact surfaces.